ANALISIS PASAR WISATA NUSANTARA DI TAMAN NASIONAL GUNUNG MERAPI PASCA TERJADINYA ERUPSI - Sinangjoyo, Nikasius Jonet (Sekolah Tinggi Pariwisata AMPTA, 2012)
This studi is aimed togive input for developing tourism at Merapi Mount National Park (TNGM) after eruption of volcano Merapi, it has goals such as : to analysis domestic and to make a marketing development strategy of this area.a collected by using quistionaire methods, interview and field observation. The sampling method was accidental sampling, with amount about 100 respondents. The data include tourist and visiting characteristic, tourist perception. Implementation could be performed by using marketing mix, wich is product, price, place and promotion. The product policy should be conducted by increasing product quality. Furthermore the pricing policy could use modified flexible pricing. The distribution policy is recommended to utilize distribution channels like community has a preference towards eco-culture and cooperation with all the components of tourism . Finally, the promotion policy should be performed by words of mouth promotions and information reported by the press. Keywords ; market, tourism marketing.